2020
DOI: 10.1039/d0tc04035e
|View full text |Cite
|
Sign up to set email alerts
|

In situ synthesis of coaxial CsPbX3@polymer (X = Cl, Br, I) fibers with significantly enhanced water stability

Abstract: Inorganic perovskites (IP) CsPbX3 (X = Cl, Br, I) have rapidly emerged as excellent candidate materials for optoelectronic devices, due to their superior optical/electronic performances. However, poor stability related to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…After the encapsulation of the peripheral polymer matrix, PAN demonstrated good oxidation resistance and hydrophobicity, which indicates good isolation of oxygen and moisture to prevent the decomposition of MAPbBr 3 PNCs and fluorescence quenching. 24,29,42 On the other hand, the high compatibility between PAN and the precursor MABr offers certain interactions between PNCs and PAN, which results in the better stability of PAN/MAPbBr 3 nanofiber films prepared by FSC.…”
Section: Stability Tests Of Pan/mapbbr 3 Nanofiber Films and Mapbbr 3...mentioning
confidence: 99%
“…After the encapsulation of the peripheral polymer matrix, PAN demonstrated good oxidation resistance and hydrophobicity, which indicates good isolation of oxygen and moisture to prevent the decomposition of MAPbBr 3 PNCs and fluorescence quenching. 24,29,42 On the other hand, the high compatibility between PAN and the precursor MABr offers certain interactions between PNCs and PAN, which results in the better stability of PAN/MAPbBr 3 nanofiber films prepared by FSC.…”
Section: Stability Tests Of Pan/mapbbr 3 Nanofiber Films and Mapbbr 3...mentioning
confidence: 99%
“…Huang et al encapsulated CsPbX 3 NCs in different polymers and prepared CsPbX 3 nanofibers by electrospinning. 5,19,46,[65][66][67][68][69][70] Here, in this review, we will describe the latest progress of CsPbX 3 perovskites and their applications in optoelectronic devices. The synthesis of CsPbX 3 perovskites in different morphologies, including single crystals, thin films and nanocrystals, are first described.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al encapsulated CsPbX 3 NCs in different polymers and prepared CsPbX 3 nanofibers by electrospinning. 5,19,46,65–70…”
Section: Introductionmentioning
confidence: 99%
“…To suppress the interaction between polyacrylonitrile (PAN) and the precursors, the perovskite precursor was injected into the inner capillary tube as the core, while PAN was fed into the outer capillary tube for achieving the encapsulation of nanocrystals. To further simplify the process, Yang’s group proposed a uniaxial electrospinning strategy for the in situ growth of all-inorganic perovskite NCs, with the assistance of oleic acid (OA) and oleylamine (OAm) as stabilizers, and demonstrated that the formation of coherent polymers strengthens the loosely bound surfactants around CsPbBr 3 NCs and protected the NCs against water and thermal treatment . However, the in situ growth of all-inorganic perovskite NCs within the polymers based on the simple uniaxial electrospinning technique without the introduction of stabilizers is still absent.…”
Section: Introductionmentioning
confidence: 99%